1974
DOI: 10.1037/h0036962
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of taste aversions induced by radiation and lithium chloride in CS-US and US-CS paradigms.

Abstract: Conditioned taste aversions induced by ionizing radiation and LiCl were compared in both forward (CS-US, conditioned stimulus-unconditioned stimulus) and backward (US-CS) conditioning paradigms. Taste aversions were produced when a saccharin CS preceded or followed a 100-r. radiation US by as much as 6 hr., but a 2% of body weight, .15 M LiCl US was effective only in CS-US pairings. It was argued that the ineffectiveness of a LiCl stimulus in US-CS pairings was not attributable to differences in the "strength"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
1
1

Year Published

1975
1975
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(53 citation statements)
references
References 17 publications
4
47
1
1
Order By: Relevance
“…In each study, the interval between lithium and subsequent taste exposure was 30 min. Previous research has shown that intraperitoneal injections of lithium suppress saccharin (Barker & Smith, 1974;Domjan, 1977) and sometimes water (Barker & Smith, 1974) consumption, starting less than 15 min after the drug treatment. These findings indicate that the malaise induced by lithium has a latency much shorter than.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In each study, the interval between lithium and subsequent taste exposure was 30 min. Previous research has shown that intraperitoneal injections of lithium suppress saccharin (Barker & Smith, 1974;Domjan, 1977) and sometimes water (Barker & Smith, 1974) consumption, starting less than 15 min after the drug treatment. These findings indicate that the malaise induced by lithium has a latency much shorter than.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, if a 30-mininjection-taste interval results in a forward pairing of taste with illness, all of the various tastes which are easily conditioned in forward conditioning paradigms also should be conditionable with backward injection-taste pairings. However, in contrast to their rapid associability with toxicosis in forward conditioning paradigms, weak concentrations of saccharin (e.g., .1% saccharin) do not become conditioned if they are presented more than 10 min after lithium injection (Barker & Smith, 1974;Dornjan & Gregg, 1977). Aversion conditioning to flavors presented longer periods after drug treatment appears to be limited to more concentrated taste solutions (Domjan & Gregg, 1977).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reversing presentation of the CS and US exposes subjects to identical stimuli, but while forward pairing of CS and US leads to associative learning, reversing the order of presentation (backward conditioning) greatly diminishes, or altogether abolishes, learning (11,19,20). Thus if convergence of CS and US information onto individual neurons characterizes the acquisition of an association, the number of cells displaying coincident activation should be significantly lower in backwardconditioned animals.…”
Section: Reversing the Order Of Cs And Us Presentation Diminishes Coimentioning
confidence: 99%